Фонопедичний метод та особливості його застосування в педагогічній роботі зі співаками неакадемічних жанрів - Карпов, В.В. (Культура народов Причерноморья, 2014)
У статті досвідченого вокального педагога й артиста йдеться про важливість збереження в належному робочому стані співочого голосу як професійного, так і самодіяльного виконавця. Звертається увага на специфіку й відповідні засоби профілактики втомлюваності чоловічих та жіночих голосів. Проблема співвідношення співочого фольклору і професіоналізму ще потребує поглибленого вивчення. При перенесенні певної фольклорної манери співу на професійну естраду не слід забувати, що ця манера, первинно не розрахована на фахову, власне щоденну експлуатацію і, невинна у побуті, може виявитися небезпечною для голосового апарату в професії. Академічна ж манера співу одразу створювалася як професійна, а відтак і вбирала в себе передусім способи захисту голосу, підвищення його витривалості, опірності навантаженню. В статье опытного вокального педагога и артиста говорится о важности сохранения в надлежащем состоянии певческого голоса как профессионального исполнителя, так и самодеятельного. Обращается внимание на специфику и соответствующие средства профилактики утомляемости мужских и женских голосов. Проблема соотношения певческого фольклора и профессионализма еще требует углубленного изучения. При переносе определенной фольклорной манеры пения на профессиональную эстраду не следует забывать, что эта манера, первично не рассчитана на профессиональную, собственно ежедневную эксплуатацию и, невинная в быту, может оказаться опасной для голосового аппарата в профессии. Академическая же манера пения сразу создавалась как профессиональная, а значит и вбирала в себя, прежде всего, способы защиты голоса, повышение его выносливости, сопротивляемости нагрузке. The experienced vocal teacher and artist writes in this article about the importance of keeping in good condition the singing voice of a professional artist and also an amateur. The attention is paid on specifics and the appropriate means of preventing fatigue male and female voices. While working with male voices it should pay particular attention to the falsetto. On falsetto voice it held the usual speech stereotype, automatically activated unwitting part of breathers. Falsetto may also be useful in the diagnostic aspect: in baritones and basses falsetto timbre is very similar with a woman's voice, and in tenors it reminds their own voice as non-falsetto register. For tenors falsetto is needed not only for the development of respiration, but also to develop skills thinning of the vocal folds, without which even with the help of the mechanism is not easy to keep the cover tessitura and sing the upper tone. There are also appropriate exercises for helping to achieve more thinning of the vocal folds, in particular blowing sound «u» on out of falsetto register. It’s useful for male voice to sing at very low tones. It cannot be forced there. Subjective perception of acoustic performance at range low tones is the most similar to the objective sound. The reason for improper sound of high notes, as a rule, lies in the thick closing and the absence of "cover". Any singing can be analyzed through the indicators of singing phonation, and accordingly, you can search and technological advices. Let’s say, female pop singing is identical to male academic: it have to work all the same protective mechanisms. But they still will not be able fully protect the female vocal apparatus from depreciation non-falsetto register. In order of prevention regular technological load helps pop singers in the academic mode: it relieves fatigue, massages apparatus, restores coordination. Phonopedistic exercises perform their curative and preventive role even without setting specific learning goals and objectives for alerting singing techniques. The problem of correlation of singing folklore and professionalism requires more in-depth study. When you transfer a certain folk style of singing on a professional platform should not be forgotten that this manner isn’t primarily intended for professional, proper daily exploitation and innocent at home, it may be dangerous for the vocal apparatus in the profession. Academic style of singing at once established as professional, and therefore absorb, primarily, methods of protection voice, increase his stamina, resistance to stress.